Are Poor Individuals Mainly Found in Poor Households? - Brown, Caitlin; Ravallion, Martin; van de Walle, Dominique (World Bank, Washington, DC, 2017)
Antipoverty policies in developing countries often assume that targeting poor households will be reasonably effective in reaching poor individuals. This paper questions this assumption, using nutritional status as a proxy for individual poverty. The comprehensive assessment for Sub-Saharan Africa reveals that undernourished women and children are spread widely across the distribution of household wealth and consumption. Roughly three-quarters of underweight women and undernourished children are not found in the poorest 20 percent of households, and around half are not found in the poorest 40 percent. The mean joint probability of being an underweight woman and living in the poorest wealth quintile is only 0.03. Countries with higher overall rates of undernutrition tend to have a higher share of undernourished individuals in nonpoor households. The results are consistent with evidence of substantial intrahousehold inequality.